The use of Grauer classification in the management of type II odontoid fracture in elderly: Prognostic factors and outcome analysis in a single centre patient series. (July 2021) - Moscolo, Fabio; Meneghelli, Pietro; Boaro, Alessandro; Impusino, Antonio; Locatelli, Francesca; Chioffi, Franco; Sala, Francesco
Highlights: The Grauer classification in the management of odontoid fractures in elderly. Surgical management achieves better clinical and radiological results. Anterior transodontoid screw obtained a 95% rate of bony-fibrous union. Forced conservative management of type IIb fractures obtained 11% rate of union. Abstract: Objective: To evaluate the results of Type II odontoid fractures management in the elderly, according to the Grauer classification. Methods: Consecutive patients with type II odontoid fracture, age > 65 years and follow-up longer than 3 months were included. Fracture management was proposed according to Grauer classification. Peri-surgical risk factors, NDI, VAS and rate of fusion were evaluated according to the treatment modality and compared between conservative and surgical groups. Results: Thirty-four patients were considered eligible for the study; 2 patients showed a Type IIa fracture, 30 patients a type IIb, and 2 patients a type IIc. Type IIa patients underwent conservative treatment that resulted in failure. A conservative management was adopted in 9 cases with type IIb due to patient preference or anaesthesiologic reasons with a treatment success at 6 months of 11%. Trans-odontoid stabilization was adopted in 21 type IIb cases with an evidence of bony or fibrous union at 6 months of 95% and a median NDI of 20%. A posterior approach was reserved for 2 type IIc fracture patients and in 6 cases as rescue surgery (bony union at 6 months of 100%; median NDI 37%). Higher Lakshmanan grade, gap and displacement of the fracture were found as significant risk factor for fracture non-union (p < 0.05). Conclusions: The surgical group presented better clinical and radiological outcome and the anterior approach proved to achieve the best results in type IIb fractures. The presence of osteoporosis and fracture spatial features should be duly considered in the decision-making process.